2015
DOI: 10.1111/jopr.12250
|View full text |Cite
|
Sign up to set email alerts
|

Position of Occlusal Plane in Dentate Patients with Reference to the Ala‐Tragal Line Using a Custom‐Made Occlusal Plane Analyzer

Abstract: The results of this study indicated that the occlusal plane was found parallel to a line joining the ala of the nose and the inferior part of the tragus in a slight majority of the participants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 36 publications
1
17
2
Order By: Relevance
“…As in the results reported here, D'Souza and Bhargava and Nissan et al also demonstrated significant variability and questionable accuracy when using Camper's plane to ascertain the occlusal plane. Significantly deviating from the present study, Shetty et al found that in all but 12% of 500 Indian patients, the occlusal plane coincided with either the superior, middle, or inferior border of the tragus. Based on their results, however, the question becomes, how does the clinician determine which landmark to use for reestablishment of the occlusal plane due to tooth loss or compromise?…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…As in the results reported here, D'Souza and Bhargava and Nissan et al also demonstrated significant variability and questionable accuracy when using Camper's plane to ascertain the occlusal plane. Significantly deviating from the present study, Shetty et al found that in all but 12% of 500 Indian patients, the occlusal plane coincided with either the superior, middle, or inferior border of the tragus. Based on their results, however, the question becomes, how does the clinician determine which landmark to use for reestablishment of the occlusal plane due to tooth loss or compromise?…”
Section: Discussioncontrasting
confidence: 99%
“…As in the results reported here, D'Souza and Bhargava 33 and Nissan et al 34 also demonstrated significant variability and questionable accuracy when using Camper's plane to ascertain the occlusal plane. Significantly deviating from the present study, Shetty et al 35 found that in all but 12% of 500 Indian patients, the Estimates and errors are given in angular degrees. All models included an intercept term, which was statistically significant p < 0.001).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The occlusal plane plays an important role in the occlusion function, stable therapeutic effect, and facial appearance, and is related to the formation mechanism of malocclusion (Marchiori et al, 2013;Shetty et al, 2015), it is often adjusted in orthodontics to achieve a stable and perfect occlusion relationship. In particular, the inclination of the posterior occlusal plane (OPP) is important for the normal physiological function of the temporomandibular joint and the growth of the mandible (Tanaka & Sato, 2008) Some authors have proposed that the cant of the maxillary posterior occlusal plane might affect the and the functional positioning of the mandible, consequently, the condyle functionally adapts to the new adopted position of the mandible (Kim et al, 2006).…”
Section: Introductionmentioning
confidence: 99%